Arsenic and old books - James, Miranda (James, Miranda. Cat in the stacks mystery., 2016)
"Lucinda Beckwith Long, the mayor of Athena, Mississippi, has donated a set of Civil War-era diaries to the archives of Athena College. She would like librarian Charlie Harris to preserve and substantiate them as part of the Long family legacy -- something that could benefit her son, Beck, as he prepares to campaign for the state senate ... Together with his Maine Coon cat, Diesel, Charlie must discover why the diaries are worth killing for -- before he too reaches his final chapter."--Back cover.